Antibacterial susceptibility testing of Mycoplasma gallisepticum isolated from poultry - AHER, T S; GANDGE, R S; BHAVE, S S (The Indian Journal of Animal Sciences, 2019)
This is the first study on antibacterial susceptibility of M. gallisepticum in Maharashtra state of India. Since the use of live mycoplasma vaccines is not widely allowed in the country; the use of antimicrobials remains the most common and effective means for controlling mycoplasma infections in poultry farms. Therefore, the current study aimed to study emergence of resistance in MG to antibacterial agents and to find out the effective antibacterial agent for treatment of CRD. In disc diffusion method, all 25 M. gallisepticum isolates were highly sensitive to tylosin followed by enrofloxacin and oxytetracycline. Till date, tylosin was the most effective therapeutic agent at lowest concentration for treatment of CRD. However, higher MIC values of isolates than ATCC strain are indication of initiation of emergence of antibacterial drug resistance in M. gallisepticum. Therefore, it is advised to select effective antibiotic based on the result of susceptibility test for the treatment of CRD to prevent further emergence of drug resistance.